Exploring the generic skills required for the employability and professional wellbeing of Pakistani Millennials: The employers' perspective - Iqbal, Jawad; Shaikh, Aliya Ahmad; Jamal, Warda Najeeb; Akhtar, Kalsoom; Rahim, Rabia; Kousar, Shazia (Frontiers in Psychology, 2023)
Introduction This study aims to elucidate the employers' perspectives on the key generic employability skills which would enable them to seek graduate jobs and will ensure their professional wellbeing once they enter the job market after acquiring a University degree. Methods In order to pursue this objective, an exploratory qualitative inquiry was deployed which involved two panel-based discussions. The respondents of each panel discussion were invited through the platforms of the Bahawalpur Chamber of Commerce and Industry (BCCI), and the Chamber of Commerce Rahim Yar Khan. These respondents represented Pharmaceuticals, Agrichemical manufacturers (fertilizers, pesticides), Livestock, Cotton, textiles, and apparel industry which are the main industries in Southern Punjab, Pakistan. Results and discussion For the purpose of analysis, a thematic analysis was done in the context of grounded theory. Resultantly, the findings of the study reveal an employers' perspective on 10 key generic employability skills as must-have for a Pakistani Millennial graduate including various soft and hard skills, such as-Emotional Intelligence, Flexibility and Adaptability, Multitasking, Computer Literacy and Digital Skills, Information Literacy and Data Analytics, Oral and Written Communication in English and Urdu, Critical Thinking, Positive Politics, Work Ethics and Professionalism, and Commercial awareness. Hence, the study produces implications for the employability stakeholders, including government and academia for a much needed shift from a mere subject-based curriculum to a skill-oriented curriculum and training in the Universities, particularly in the region of Southern Punjab, and all across Pakistan as well.